北太平洋至西北冰洋多环芳烃的海-气界面过程研究 - 陈勉 (2018)
于中国第4次和第6次北极科考期间采用主、被动不同采样方法采集了北太平洋至西北冰洋大气和海水中多环芳烃（PolycyclicAromaticHydrocarbons，PAHs）样品，获得了大空间尺度上PAHs在大气和表层海水中的含量、分布和来源及北冰洋中心海区PAHs的垂直分布特征等生物地球化学特征，探讨了PAHs的海-气界面过程，主要初步结论如下： 2010年7-9月第4次北极科考期间，采用主动采样方法采集了表层海水和北冰洋中心海盆区垂直站位PAHs样品。表层海水中溶解态Σ7PAH浓度范围为1.08-5.25ng/L，平均浓度为2.00ng/L，总体上呈现出从北太平洋到西北冰洋浓度逐渐下降的. Polycyclic Aromatic Hydrocarbons (PAHs) in the air and seawaters were collected during the 4th and 6th Chinese National Arctic Research Expedition. Distribution and sources of PAHs from the North Pacific to the Western Arctic, vertical profile in the Arctic, as well as air-sea interface process were discussed. The main conclusions are as followed: PAHs in the surface seawaters from the North Paci. 学位：理学硕士 院系专业：海洋与地球学院_海洋化学 学号：22320141151301